La figure très hellénistique d’Iphigénie dans l’Alexandra de Lycophron… Quels parallèles dans l’iconographie ? - Christophe Cusset; Pascale Linant de Bellefonds (Aitia, 2015)
Iphigeneia can be conceived of as a very Hellenistic figure: her fate and several of her features were indeed very likely to become a matter of deep interest for the Hellenistic poet-scholars who keenly studied recondite mythological details and alternative versions of myths. In the 3rd century BC, the legend of Iphigeneia was still a matter of debate: her name, her genealogy, the circumstances of her sacrifice and her whereabouts after the sacrifice were uncertain and were known through different versions of the myth. As the first victim of the Greek expedition against Troy, she was also bound to find an important place in Lycophron’s Alexandra. In Cassandra’s prophecy, Iphigeneia could easily become the Greek pendant to Cassandra’s personal tragedy. This paper will analyse the characteristics of the version chosen by Lycophron and set it against the better-known version of the myth known through the tragedies of Euripides. It will then explore the possible parallels to the version chosen by Lycophron in ancient iconography.